Note: Enter your answer and show all the steps that you use to solve this problem in the space provided.

Simplify the following expression.

4(20+12)÷(5−3)
show your work

1 answer

To simplify the expression 4(20+12)÷(5-3), we need to follow the order of operations (PEMDAS).

First, we simplify the expression inside the parentheses: 20+12 = 32.

Next, we multiply 4 by 32: 4(32) = 128.

Then, we simplify the expression inside the second set of parentheses: 5-3 = 2.

Finally, we divide 128 by 2: 128 ÷ 2 = 64.

Therefore, the simplified expression is 64.